Voices in the dark interviews with horror writers, directors and actors - Kane, Paul, 1973-; O'Regan, Marie; Billson, Anne (McFarland & Co., Inc., Publishers, 2011)
"Covering supernatural fiction to graphic horror, these interviewees discuss the creative challenges, expectations and conventions of the genre. These authors, directors and actors working in the horror genre include Clive Barker, Neil Gaiman, James Herbert, Joe Hill, Steve Niles, Sarah Pinborough, John Carpenter, Mick Garris, Stuart Gordon, Rob Zombie, Christa Campbell, Zach Galligan, Betsy Palmer and Ron Perlman"--Provided by publisher.